Hyphal Growth in Human Fungal Pathogens and Its Role in Virulence - Alexandra Brand (International Journal of Microbiology, 2012)
Most of the fungal species that infect humans can grow in more than one morphological form but only a subset of pathogens produce filamentous hyphae during the infection process. This subset is phylogenetically unrelated and includes the commonly carried yeasts, Candida albicans, C. dubliniensis, and Malassezia spp., and the acquired pathogens, Aspergillus fumigatus and dermatophytes such as Trichophyton rubrum and T. mentagrophytes. The primary function of hypha formation in these opportunistic pathogens is to invade the substrate they are adhered to, whether biotic or abiotic, but other functions include the directional translocation between host environments, consolidation of the colony, nutrient acquisition and the formation of 3-dimensional matrices. To support these functions, polarised hyphal growth is co-regulated with other factors that are essential for normal hypha function in vivo.